2015
DOI: 10.1177/1098612x15600481
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis in a domestic shorthair cat

Abstract: A 3-year-old male castrated domestic shorthair cat was presented with an acute history of lethargy and decreased appetite. Pertinent physical examination abnormalities included palpable irregularity of the right kidney and pain on palpation of the left kidney. Ultrasonographic imaging of the abdomen revealed gas present at the corticomedullary junction of the left kidney, consistent with emphysematous pyelonephritis, as well as emphysematous cystitis. While quantitative urine culture via pyelocentesis yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The diagnosis remains challenging and information in the literature is limited to a small number of case reports. 68,69…”
Section: Clinical Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis remains challenging and information in the literature is limited to a small number of case reports. 68,69…”
Section: Clinical Signsmentioning
confidence: 99%
“…The diagnosis remains challenging and information in the literature is limited to a small number of case reports. 68,69 Acute pyelo nephritis may be associated with distinct clinical signs such as fever and painful kidneys, as well as anorexia, lethargy, polyuria and polydipsia, vomiting and diarrhoea. 70 According to one study of 17 histopathologically confirmed cases of pyelonephritis, the most common clinical signs were non-specific, such as anorexia, lethargy and vomiting; 71 renal pain and pyrexia were only observed in 3/17 and 2/17 cats, respectively.…”
Section: Upper Utimentioning
confidence: 99%
“…Patients may be asymptomatic or showing signs associated to their underlying diseases. It should be taken into consideration that EP and peritonitis have been reported as consequences of EC in dogs, cats, and humans,1,7,8,12,16 and in human medicine, a case of severe sepsis secondary to EC has been described 18. Early detection of EC is therefore of utter importance; therefore, greater attention is required on the presence of risk factors for EC.…”
Section: Clinical Signs and Laboratory Findingsmentioning
confidence: 99%
“…Antibiogram should then be performed, in order to implement effective antibiotic therapy. In the reported cases of EC in veterinary medicine, cultures have been achieved from samples collected via cystocentesis, sterile catheterization or, in few cases, by mid-stream voiding 4,5,7–9,12–14,16. Cystocentesis is a simple but invasive form of paracentesis used to obtain sterile urine samples; it has been reported that in some cases, a few bubbles of air entrapped in the wall bladder can be detected after this procedure 17.…”
Section: Clinical Signs and Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation